EPEN-03. ZFTA/C11ORF95 FUSIONS DRIVE SUPRATENTORIAL EPENDYMOMA VIA SHARED ONCOGENIC MECHANISMS. (1st June 2021) - Zheng, Tuyu; Ghasemi, David R; Okonechnikov, Konstantin; Korshunov, Andrey; Maaß, Kendra K; Sill, Martin; Gojo, Johannes; Schüller, Ulrich; Milde, Till; Mack, Stephen C; Gilbertson, Richard J; von Deimling, Andreas; et al.
Abstract: The majority of supratentorial ependymomas (ST-EPN) are driven by fusion genes between RELA and zinc finger translocation associated, ZFTA, previously named C11orf95 . Apart from fusions with a portion of the Hippo effector YAP1, which affects a small group of infant patients, the oncogenic mechanism of remaining ST-EPNs remains unclear. Aiming at refining the molecular classification of ST-EPNs, we have analyzed methylation profiles, RNA and DNA sequencing results as well as clinical data in a cohort of 613 ST-EPNs. An unbiased approach revealed distinct methylation clusters composed of tumors with ependymal but also various other histological features containing alternative translocations that shared ZFTA as a partner gene. Tumors within these additional clusters were characterized by fusions of ZFTA to numerous fusion partners different from RELA, e.g. MAML2, MAML3, NCOA2 and SS18, implying a general role of ZFTA in tumorigenesis of ST-EPN. Indeed, the transforming capacity of newly identified fusion genes was validated using an electroporation-based in vivo gene transfer technology in mice. All fusion genes themselves were sufficient to drive malignant transformation in the developing cerebral cortex and resulting tumors faithfully recapitulated molecular characteristics of their human counterparts. We found that both, the partner gene and the zinc finger DNA binding domain of ZFTA, were essential to exert tumorigenesis. Together with two additional studies, we performed a comprehensive analysis across datasets to derive a 93 gene signature of ZFTA-RELA-driven tumors, in which the Sonic Hedgehog effector gene GLI2 was identified as a promising downstream target. Subsequent co-expression of ZFTA:RELA and a dominant negative form of Gli2 indeed hampered tumorigenesis. Targeting GLI2 with arsenic trioxide caused extended survival of tumor-bearing animals, indicating GLI2 as a critical regulator of ZFTA fusion-positive tumorigenesis as well as a potential therapeutic vulnerability in these tumors.